Paediatric out-of-hospital cardiac arrests in Melbourne, Australia: Improved reporting by adding coronial data to a cardiac arrest registry - Deasy, C.; Hall, D.; Bray, Janet; Smith, K.; Bernard, S.; Cameron, P. (2013)
Aim We describe improved reporting of paediatric out-of-hospital cardiac arrest (OHCA) by adding coronial findings to a cardiac arrest registry. Methods Non-traumatic OHCA occurring in paediatric patients aged less than 16 years were identified using the Victorian Ambulance Cardiac Arrest Registry and available coronial findings reviewed. Results Between the years 2001 and 2009, emergency medical services (EMS) attended 26 974 non-traumatic OHCA of which 390 (1.4%) occurred in children less than 16 years of age. We successfully linked 301 patients with the coronial registry; excluding patients discharged alive from hospital (n=22) and patients with terminal illness (n=16), this represents 86% of OHCA attended by the ambulance. Agreement between the paramedic cause of OHCA and the coronial cause of death was 66.5% (? 0.16) for presumed cardiac, 74.4% (? 0.43) for sudden infant death syndrome (SIDS), 81.1% (? 0.17) for respiratory, 92.7% (? 0.18) for neurological and 98.3% (? 0.27) for drug overdose precipitants to OHCA. Undiagnosed congenital heart disease was a rare cause of OHCA (n=3, 1%). Intentional injury was found on autopsy in 13 cases; six cases were clinically thought to be SIDS and two cases presumed cardiac. Co-sleeping was found in 35 cases (39%) of SIDS. Conclusions This study highlights the limitations associated with ascribing the cause of OHCA on the basis of clinical details. Improved reporting is possible by linkage with coronial data. Such robust data inform EMS service providers but also the wider healthcare system where preventive, diagnostic and treatment strategies can be maximised.